PROBABLE MODE OF ACTION OF STHANIKA CHIKITISA (LOCAL TREATMENT) IN YONIVYAPADA - AN AYURVEDIC INSIGHT - Meena, Parmar; Gaurav, Parmar (International Journal of Ayurveda and Pharma Research, 2015)
The physiology of reproductive system of women is different from her male partner to a greater extent as she has to punctuate many functions like, achievement of conception, child birth etc. These physiological changes make her prone to pathological disorders. Thats why reproductive health is just as important as other aspects of health. In classics, for the management of various Yonivyapadas (gynaecological disorders) the Sthanika chikitsa (local treatment) i.e. Douching, Tampooning per vaginum, local use of pessaries and fumigation has been mentioned and is effective in curing the diseases. But, how these drugs act has not widely explained. As vaginal administration of drug gain recognition as a potential route for drug delivery, thats why it is important to pay attention that how the drug act through vagina.